Analisis Pengaruh Komitmen, Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai Dinas Kependudukan dan Catatan Sipil Kabupaten Pasaman Barat - Muhammad Jamil (Majalah Ilmiah UPI YPTK, 2019)
This study aims to reveal. (1) Analysis of the influence of Commitments on employee performance, (2) Work Environment on employee performance, (3) Work Discipline on employee performance, (4) Analysis of the Effect of Commitment, Work Environment and Work Discipline and simultaneously on Employee Performance. The population of this study were all employees at the Population and Civil Registration Office of West Pasaman Regency, amounting to 58 people. Samples were taken from all populations, namely 58 people. The analysis method uses multiple regression analysis. Research Results obtained 1) Commitment variables, work environment and work discipline simultaneously have a positive and significant effect on the performance of the Civil Registration and Civil Registration Service Office of West Pasaman Regency. The contribution of commitment variables, work environment and work discipline to employee performance is 51.6%, while the remaining 48.4% is influenced by other variables not included in the scope of this research. 2. Commitment variables, work environment and work discipline partial has a positive and significant effect on the performance of the Civil Servants and Civil Registration Offices of West Pasaman Regency